Men of blood violence, manliness and criminal justice in Victorian England - Wiener, Martin J. 1941- (Cambridge Univ. Press, 2006)
This book examines far more thoroughly than ever before the treatment of serious violence by men against women in 19th-century England. During Victoria's reign the criminal law came to punish such violence more systematically and heavily, while propagating a new, more pacific ideal of manliness. Yet this apparently progressive legal development called forth strong resistance, not only from violent men themselves but from others who drew upon discourses of democracy, humanitarianism and patriarchy to establish sympathy with "men of blood." In exploring this development and the contest it generated, Wiener analyzes the cultural logic underlying shifting practices in 19th-century courts and Whitehall and locates competing cultural discourses in the everyday life of criminal justice. The tensions and dilemmas highlighted by this book are more than simply "Victorian" ones; to an important degree they remain with us. Consequently this work speaks not only to historians and to students of gender but also to criminologists and legal theorists.--Back cover.
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Geschichte 1832-1902; Frau; Geschichte; Criminal justice, Administration of -- England -- History -- 19th century; Homicide -- England -- History -- 19th century; Sexism -- England -- History -- 19th century; Violence in men -- England -- History -- 19th century; Wife abuse -- England -- History -- 19th century; Women -- Violence against -- England -- History -- 19th century; Rechtsprechung; Mann; Gewalt; Großbritannien